IKAN CUPANG SEBAGAI METAFORA DALAM KARYA SENI PATUNG ABSTRAK FIGURATIF - RIKO AWADER. AS, Dra. Lisa Widiarti, M.Sn., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose in making this final work is to visualize betta fish as a metaphor of  uman behavior, which deviates in society today, through the work of figurative  bstract sculpture. The methods used in making this work are: 1) the preparation stage of observation, 2) elaboration, 3) the synthesis stage, 4) the realization of the concept that begins to make sketches, the process of work, and finising. 5) the stages in the exhibition are cataloging for works to be exhibited, displaying works in the room to be used for exhibition works, providing guestbooks, and ready for   hibition opening. The results of the discussion terwujutlah seven sculptures that provide information and media learning in everyday life as stipulated in the sculpture entitled: 1. Arogan, 2. Show, 3. Individual, 4. Selfish, 5. Ruler, 6. Suppression, 7. Fighting.Kata kunci : Ikan Cupang, metafora, seni patung, abstrak figuratif